Banach spaces with the Blum-Hanson Property - Netillard , Francois (North-Western European Journal of Mathematics, 2022)
We are interested in a sufficient condition given in an article by P. Lefèvre, É. Matheron and A. Primot to obtain the Blum-Hanson property and we then partially answer two questions asked in this same article on other possible conditions to have this property for a separable Banach space.